Reconstructing Europe: The Need for Guidelines. (October 2013) - Bold, John; Pickard, Robert
Abstract : In a contemporary climate in which reconstruction in a historicist style is regarded negatively by heritage specialists as inauthentic, there is a need for better guidance and greater clarity about what reconstruction connotes, when it is admissible to carry it out in a style or form reflecting so far as possible what has been lost, how it should be done, and what authenticity actually means. In this paper, we review the current situation and existing charters and terminology, and suggest ways forward. Experience within the Council of Europe has shown that reconstruction after the wars in the former Yugoslavia will take place whether or not it is approved by the international heritage community. Guidelines are needed and we suggest in an Appendix the form which these might take.